Parental and peer attachment, self-value and spirituality as predictors of counselling attitudes among Nigerian students in Malaysian universities - Idowu, Grace Tanimoonwo (2016)
There is mounting evidence that attitude is one of the indispensable tools to succeed in life. Counseling attitudes involve reflecting on oneself and being able to systematically analyze one‟s situation in order to make acceptable decisions at any point in time. It also allows for a clearly defined connection to others in any part of the world. The main purpose of this study is to examine parental and peer attachment, self-value, and spirituality as predictors of counseling attitudes among Nigerian students in Malaysian universities. To illuminate the counseling attitudes concept and potential in a concrete context, this study: 1.) identifies four psychological factors affecting counseling attitudes among Nigerian students in Malaysian universities, 2) determines the direct relationships between parental and peer attachment, self-value, spirituality and counseling attitudes among the sample population, 3) explores the attitudes toward seeking professional psychological help among Nigerian students in selected Malaysian universities, 4) determines the mediating relationships existing between parental and peer attachment, counseling attitudes and self-value through spirituality, 5) To determine whether parental and peer attachment, self-value and spirituality predict counseling attitudes among Nigerian students in Malaysian universities; using the attachment perspectives of Bowlby (1969), and the personcentered theory of self by Rogers (1951), to analyze and explain the interaction among the variables. The study was designed into three phases. The first phase was a pilot study of the focus sample. The sample size for this phase was 50 students from Universiti Putra Malaysia (UPM). The second phase was an exploratory factor analysis (EFA) consisting of 200 students randomly selected from the sample population. The third phase was the main research, a descriptive and correlational quantitative study involving ten randomly selected universities in Malaysia. A sampling size of 394 students, both male and female, was systematically drawn from the population of the Nigerian students in these ten universities. Sources of the five instruments used to quantify the tests assertions, using a check-list and rating scales involved: The Inventory of Parent and Peer Attachment (IPPA: Armsden and Greenberg, 1987), Attitude towards Seeking Professional Psychological Help-Short Form (ATSPPHS-SF; Fischer & Farina (1995), Self-Spirituality Personality Inventory (SSPI) adapted from Universal Religious Personality Inventory (Idris & Azimi, 2008), Self-Value Rating Scale (SVRS) adapted from Self-Esteem Rating Scales (SERS: Nugent & Thomas, 1993) and the Self-Worth Quiz of Edith Cowan University (ECU, 2010) in Australia. Also, a demographic survey was included to obtain data about the respondents‟ gender, age, name of school, family/religious background, closest person (attached to), year of stay in Malaysia, and state of origin. The collected data were coded and then analyzed using the Statistical Package for Social Sciences (SPSS) software version 21 and AMOS Structural Equation Modeling (SEM). The result from the data analysis shows that through spirituality, there was a partial mediation in the relationships between parental attachment and counseling attitudes. Also, there was a partial mediation between self-value and counseling attitudes through spirituality, but no significant mediation was found between peer attachment and counseling attitudes. In addition, the results indicated that stigmatization and interpersonal openness are obstacles to seeking professional counseling services among the university students. The overall analysis of the data revealed that all except one hypothesis in this study were supported by the results of the empirical evidence. This study theoretically supports the integration of the structural model and the key concepts of counseling attitudes among Nigerian students in Malaysian universities. Findings on parental and peer attachment strengthens the notion that Nigerian students are entwined with their families and friends, probably because of the financial supports from their parents and moral support from their friends, due to the psychologically-distressed environment they found themselves, being away from home and other familiar terrains. In conclusion, parental and peer attachment, self-value and spirituality are predictors of counseling attitudes among Nigerian students in Malaysian universities. Practically, the findings of the study have implications for Guidance Counselors, Educators, Trainers and other researchers in the field of Counseling Psychology because through the selected factors, the study gives an understanding on the sample population and also illuminates paradigm of spirituality and how Christianity and Islamic spirituality are both relevant in solving counseling problems. Also as an additional policy, that procures a solid solution to the problems of non-conformity of youths to laid-down norms of the society; boosting their counseling attitudes through spirituality because the study linked parental and peer attachment and self-value to the creation of positive counseling attitudes among students in the Diaspora. Future studies of different populations may be carried out to reprise the findings and for generalization.